2022
DOI: 10.1111/ics.12797
|View full text |Cite
|
Sign up to set email alerts
|

From decoding the perception of tightness to a clinical proof of soothing effects derived from natural ingredients in a moisturizer

Abstract: Objective To decode the feeling of skin tightness after application of a cosmetic product and how to soothe this discomfort. To pursue this aim, we considered the ingredient's effect on stratum corneum (SC) biomechanics to differentiate between consumers prone to tightness from those that are not and correlate these effects with mechanoreceptor activation. Methods In vivo clinical trials were used to assess the tightness perception dichotomy between groups of Caucasian women; in vitro experiments were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The reason why tactile perception changes with increasing skin deformation remains unknown and should be investigated in the future. Skin mechanical properties (e.g., stiffness ratio or viscoelasticity of each layer) that increase the amount of skin deformation in response to mechanical stimuli may change the tactile stimuli received by the mechanoreceptors 29,43,44 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason why tactile perception changes with increasing skin deformation remains unknown and should be investigated in the future. Skin mechanical properties (e.g., stiffness ratio or viscoelasticity of each layer) that increase the amount of skin deformation in response to mechanical stimuli may change the tactile stimuli received by the mechanoreceptors 29,43,44 …”
Section: Discussionmentioning
confidence: 99%
“…Skin mechanical properties (e.g., stiffness ratio or viscoelasticity of each layer) that increase the amount of skin deformation in response to mechanical stimuli may change the tactile stimuli received by the mechanoreceptors. 29,43,44 Small skin deformations during tactile perception may reflect individual differences in the sensory nervous system, leading to interindividual variations in threshold values. The previous section indicated that the magnitude of skin deformation may be related to the subtlety of tactile perception; however, we observed interindividual variations in the stimulus threshold when the peak skin deformations were smaller than 0.36 mm.…”
Section: Discussionmentioning
confidence: 99%
“…measured on cheek with Corneometer CM825 Courage & Khazaka). Previous studies demonstrated that formulas containing high concentration of glycerol allowed a strong 19 and long‐lasting 20 moisturizing effect. Therefore, a 20% glycerol in oil/water (O/W) emulsion was applied twice daily on split face versus an O/W emulsion placebo for 4 months.…”
Section: Methodsmentioning
confidence: 99%
“…measured on cheek with Corneometer CM825 Courage & Khazaka). Previous studies demonstrated that formulas containing high concentration of glycerol allowed a strong 19 and long-lasting 20 (Courage + Khazaka electronic GmbH, Cologne, Germany). For the DTM, which is rather sensitive to the skin superficial layers, the torque applied to the skin was 100 cN cm.…”
Section: Clinical Studymentioning
confidence: 99%
“…Although a straightforward relationship between subjective consumer tactile perception and a particular ingredient in a formulation is far from being understood, it is well established that low adhesion and friction are desirable physicochemical characteristics. 13,14 Therefore, tools which can be used to fundamentally understand these characteristics will be invaluable to reformulation.…”
Section: Introductionmentioning
confidence: 99%